2015
DOI: 10.1002/2014gc005658
|View full text |Cite
|
Sign up to set email alerts
|

A global model for cave ventilation and seasonal bias in speleothem paleoclimate records

Abstract: Cave calcite deposits (speleothems) provide long and continuous records of paleoenvironmental conditions in terrestrial settings. Typical environmental proxy measurements include speleothem growth rate and variations in elemental and isotope geochemistry. Commonly the assumption is made that speleothems grow continuously and at a constant rate throughout the year. However, seasonal variation of growth rate may be the rule in many caves. Here we apply observations of modern calcite growth and cave-air CO 2 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 32 publications
5
50
2
1
Order By: Relevance
“…There exist roughly twice as many groundwater reconstructions of late-glacial to late-Holocene precipitation δ 18 O shifts (n = 59) as the combined total of speleothem and ice core records (n = 27; where δ 18 O = ( 18 O / 16 O sample ) / ( 18 O / 16 O standard mean ocean water -1) × 1000). A recent global synthesis of paired precipitationgroundwater isotopic data demonstrated that modern annual precipitation and modern groundwater isotope compositions follow systematic relationships with some bias toward winter and wet-season precipitation (Jasechko et al, 2014). Systematic rainfall-recharge relationships shown by Jasechko et al (2014) support our primary assumption in this study that groundwater isotope compositions closely reflect meteoric water.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…There exist roughly twice as many groundwater reconstructions of late-glacial to late-Holocene precipitation δ 18 O shifts (n = 59) as the combined total of speleothem and ice core records (n = 27; where δ 18 O = ( 18 O / 16 O sample ) / ( 18 O / 16 O standard mean ocean water -1) × 1000). A recent global synthesis of paired precipitationgroundwater isotopic data demonstrated that modern annual precipitation and modern groundwater isotope compositions follow systematic relationships with some bias toward winter and wet-season precipitation (Jasechko et al, 2014). Systematic rainfall-recharge relationships shown by Jasechko et al (2014) support our primary assumption in this study that groundwater isotope compositions closely reflect meteoric water.…”
supporting
confidence: 79%
“…A recent global synthesis of paired precipitationgroundwater isotopic data demonstrated that modern annual precipitation and modern groundwater isotope compositions follow systematic relationships with some bias toward winter and wet-season precipitation (Jasechko et al, 2014). Systematic rainfall-recharge relationships shown by Jasechko et al (2014) support our primary assumption in this study that groundwater isotope compositions closely reflect meteoric water. Because groundwater records can only identify climate change occurring over thousands of years due to hydrodynamic dispersion during multi-millennial residence times (e.g., Davison and Airey, 1982;Stute and Deak, 1989), we limit the focus of this study to meteoric water isotope composition changes from the latter half of the last glacial time period to the late-Holocene.…”
supporting
confidence: 79%
“…A similar seasonal pattern of the composition of cave atmosphere and its gas exchange with exterior has been previously study by James et al (2015). The process is also confirmed by the 222 Rn concentration, a good indicator of the connexion between the subterranean environment and the atmosphere (Valladares et al, 2014), which, simultaneously to the CO2, suffers a sharp decrease as consequence of the ventilation.…”
supporting
confidence: 77%
“…Seasonally alternating stability of the cave atmosphere, as produced by local convection (Fig. 4e), has recently been used to explain seasonal changes in CO 2 concentrations in caves and other subsurface voids that display low CO 2 concentrations in the winter and high concentrations in the summer (Banner et al 2007;Weisbrod et al 2009;Serrano-Ortiz et al 2010;Breecker et al 2012;James et al 2015). It is inferred that the voids have higher exchange rates with the surface atmosphere during winter than in summer.…”
Section: Carbon Dioxide Dynamics Within Karstmentioning
confidence: 99%